THE PSYCHOLOGY OF CELEBRITY ENDORSEMENTS AND CONSUMER PURCHASING - Smith, Emily Johnson; Brown , Alexander Michael; Patel, Olivia Katherine (Current Journal of Humanities, Arts and Social Sciences (CJHASS), 2023)
Celebrities wield a unique power in modern society, capturing public attention and evoking strong emotions. While some celebrities may be uncomfortable with constant scrutiny, brands eagerly seek the limelight they provide. In the competitive market landscape, achieving popularity equates to possessing a formidable influence over public perception and preferences. This study examines the symbiotic relationship between celebrities and brands, focusing on the mechanism through which celebrities facilitate brand popularity. The connection between celebrities and the public is founded on trust, admiration, and emulation. People aspire to emulate their favorite stars, aligning their preferences and behaviors with those of celebrities. This includes emulating fashion choices, grooming habits, and lifestyle preferences endorsed by these admired figures. Such celebrity-driven trends gain consumer confidence by leveraging the established appeal of well-known personalities. Celebrity endorsements wield substantial influence in advertising campaigns. The presence of a celebrity in a brand’s promotional materials instantly garners attention, accelerating brand recognition. Whether through visuals in advertisements or verbal endorsements in television spots, the involvement of a celebrity bolsters the credibility and memorability of a product. Just as celebrities breathe life into characters on screen, they infuse narratives into brand stories, enhancing consumer engagement. In the contemporary market landscape, celebrity endorsements have emerged as a pivotal strategy for brand promotion. Firms diligently deploy these partnerships to sustain and amplify their brand equity. This research delves into the dynamics of celebrity endorsement, shedding light on its pivotal role in brand promotion and popularity enhancement.